2019
DOI: 10.1039/c9qi00507b
|View full text |Cite
|
Sign up to set email alerts
|

High-capacity organic sodium ion batteries using a sustainable C4Q/CMK-3/SWCNT electrode

Abstract: SWCNTs formed a three-dimensional conductive network between C4Q/CMK-3 nanocomposites, significantly improving the electrochemical performance of C4Q-SIBs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 31 publications
1
38
1
Order By: Relevance
“…Up to now, organic small molecules with different groups, including CO (quinones and ketones, carboxylates, anhydrides, and imides derivatives), CN (Schiff, pteridine derivatives), and NN (azo derivatives) bond compounds, have been proved to be electroactive electrode materials for SIBs. Among them, the carbonyl compounds containing CO bond is the most widely studied organic electrode materials, because of their unique multielectron reaction, high theoretical capacity and a wide structural diversity . Schiff and pteridine derivatives containing CN bond has an adjustable electrochemical activity, in which plane structure and conjugated structure play an important role in stabilizing their electrochemical activity .…”
Section: Research Progress Of Organic Electrode Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Up to now, organic small molecules with different groups, including CO (quinones and ketones, carboxylates, anhydrides, and imides derivatives), CN (Schiff, pteridine derivatives), and NN (azo derivatives) bond compounds, have been proved to be electroactive electrode materials for SIBs. Among them, the carbonyl compounds containing CO bond is the most widely studied organic electrode materials, because of their unique multielectron reaction, high theoretical capacity and a wide structural diversity . Schiff and pteridine derivatives containing CN bond has an adjustable electrochemical activity, in which plane structure and conjugated structure play an important role in stabilizing their electrochemical activity .…”
Section: Research Progress Of Organic Electrode Materialsmentioning
confidence: 99%
“…Particularly the application of new azo compounds and MOFs as OSIB materials are also included in this review. Among them, organic small‐molecular materials include mainly three different classes: carbonyl compounds (CO), Schiff and pteridine derivatives (CN), and azo derivatives (NN) . In carbonyl (CO) compounds, quinones and ketones demonstrate higher redox potential, carboxylic acids however possess lower Na insertion voltage, while the anhydride compounds are recognized by their high specific capacity and long cycle life.…”
Section: Introductionmentioning
confidence: 99%
“…These results demonstrate that immobilizing active materials by carbon materials also has excellent effects on enhancing the electrochemical properties of SIBs. In addition, the ternary composite C4Q/CMK‐3/SWCNTs also can be applied to SIBs . For the first cycle at 0.1 C, the capacity was 441 mAh g −1 and remained 75 % after 50 cycles.…”
Section: Applications In Sibsmentioning
confidence: 99%
“…Reproduced by permission of The Royal Society of Chemistry. b) Cycle performance of C4Q/CMK‐3/SWCNTs composite . Reproduced by permission of The Royal Society of Chemistry.…”
Section: Applications In Sibsmentioning
confidence: 99%
“…Nevertheless, the high volatility and solubility [28] of quinone greatly limit its usage in LIBs. Up to now, anthraquinone (AQ) [28], dibenzothiophene (DBT) [28], calix[4]quinone (C4Q) [29][30][31][32], pillar[5]quinone (P5Q) [33,34] and several other quinones derivatives have been widely reported. Huang et al [29] first applied C4Q as cathode in LIBs and found that C4Q could deliver an initial capacity of 431 mA h g −1 (97% of C theo ) in the liquid electrolytes; however, the batteries only preserved a capacity approximating to 100 mA h g −1 after five cycles.…”
Section: Introductionmentioning
confidence: 99%